MANAGEMENT OF ENVIRONMENTALLY SOUND AREAS WITH ADIWIYATA PROGRAM THROUGH EMPOWERMENT OF ELEMENTARY SCHOOL TEACHERS: PENGELOLAAN KAWASAN BERWAWASAN LINGKUNGAN DENGAN PROGRAM ADIWIYATA MELALUI PEMBERDAYAAN GURU-GURU SD - Jajuk Herawati; Dwie Retna Suryaningsih; Indarwati Indarwati (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Environmental problems are problems that arise from humans themselves, this can be one of the obstacles to factors that affect the success of teachers and learners in the teaching and learning process in schools. This problem must be overcome by making an effort to foster attitudes and living behaviors for school residents, both teachers, students, employees and parents / families who care about the environment with the management of environmentally sound school areas through the Adiwiyata program. Adiwiyata Program is a program of the Ministry of Environment, where this program is a form of appreciation given by the government to formal educational institutions that are considered to be instrumental in developing environmental education. With the Adiwiyata program, the Faculty of Agriculture – Universitas Wijaya Kusuma Surabaya as one of the Universities in Indonesia, especially East Java can make a real contribution in the success of the program through Community Service (PkM) activities. Community Service activities with the empowerment of elementary school teachers are carried out in the West Surabaya area, which is structurally an integral part of the Lakarsantri Subdistrict area, Surabaya - East Java. This program aims to grow and improve the ability of elementary school students to create a healthy environment and avoid negative environmental impacts through school activities with the empowerment of elementary teachers, through active involvement both initiativeally and participatoryly. This method of activity will be carried out using the PRRA (Participatory Rapid Rural Appraissal) and RRA (Rapid and Rural Appraissal) methods, between members of the elementary and companion teachers group (UWKS College) and students. This PkM is important to be proposed and carried out in order to support accelerating the target of achieving the UWKS Higher Education Strategic Plan, where the Umbrella of UWKS Superior Research and Service in accordance with the Rector's Decree in 2012, that the umbrella of research and service of the flagship LPPM-UWKS institution is "Sainteks and Environmental Insights". Where the flagship umbrella of this institution is the basic reference for lecturers to develop self-reliance and creativity, in compiling devotional activities at UWKS. The proposed and will be done service is partly an application of the author's superior research results, where the author's research results have been selected as a national finalist of PT's flagship research products in 2013, as well as a concrete step in realizing the vision and mission of the University, as proclaimed in the UWKS Strategic Plan, is also one of the solutions in solving community problems in facing this pandemic